The influence of various cooking methods on the antioxidant compounds of local carrot variety (Daucus carota) cultivated in Jaffna District - Thanuja, S.; Sivakanthan, S.; Vasantharuba, S. (University of Jaffna, 2018)
Carrot (Daucus carota) is a rich source of antioxidants, mainly, β-carotene and phenolics, which are necessary to maintain eye health and prevent some types of cancers. Aim of this study was to evaluate the effect of cooking methods such as boiling, stir-frying and microwave cooking on the antioxidant potential of local carrot variety. The influence of different cooking methods on the total phenolic content (TPC), total flavonoid content (TFC), total antioxidant capacity (TAC) and antioxidant activity (2, 2-Diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity expressed as IC50 value, which is inversely proportional to antioxidant activity) of carrot was evaluated. Boiling did not have significant effect on TPC and TFC, while microwave cooking increased the TFC significantly. All cooking methods caused significant changes in the TPC except boiling. Stir-fried carrot showed significantly lower TPC, TFC and TAC than carrot cooked by other two methods except for TAC of boiled carrot. Stir-frying did not change the DPPH radical scavenging activity, while microwave cooking and boiling reduced DPPH radical scavenging activity. Microwave cooking found to be the better method than other two methods to preserve or enhance the antioxidant compounds of carrot. Keywords - antioxidants, carrot, flavonoid content, phenolic content, radical scavenging activity.